Economic Effects of Covid-19 on the Indian Carpet Industry. (3rd July 2022) - Alam, Mahfooz
Abstract: The Indian carpet industry has great potential in the economic development of the nation. This agri-based, unorganized sector employs millions of skilled and unskilled labors and acts as a source for their livelihood. The present study provides an overview of the impact of Covid-19 on the Indian carpet industry, discusses the export performance and vulnerabilities of the workers employed, identify certain export market strategies for the overall prosperity of the carpet industry. The Indian carpet industry has to pay a heavy price in the lockdown and the condition of the carpet industry is still deplorable. The sluggish demand for carpet across developed nations, closure of the production centers followed by phased lockdowns in the country and the migration of skilled labors/weavers added to its woes. The carpet industry is experiencing a tough time and it is evident with an abrupt decline in the export volumes and values of trade. To develop a strategic policy and provide job security to the workers employed in precarious jobs is the need of the hour.